The spatial separation of electron-hole pairs in Si/Ge heterostructures - Lysenko, V.S.; Kondratenko, S.V.; Melnichuk, Ye.Ye.; Terebinska, M.I.; Tkachuk, O.I.; Kozyrev, Yu.N.; Lobanov, V.V. (Поверхность, 2015)
Photogeneration and transport of nonequilibrium charge carriers, and the determination of photoresponce mechanisms in semiconductor SiGe/Si and SiGe/SiO₂/p-Si heterostructures with nanoisland were investigated. The structures were grown by molecular beam epitaxy technique. The work generalizes the results of studies of morphological, structural, optical and electrical properties of heterostructures with nanoscale objects – quantum dots and quantum wells. It is shown that the photoconductivity of nanoheterostructures SiGe/Si in the infrared range depending on the component composition, size and magnitude of the mechanical stresses in nanoislands Si1-xGex is determined by interband and intraband transitions involving localized states of the valence band of the Ge nanoscale objects. The effects of long-decay photoconductivity and optical quenching of conductivity in SiGe/SiO₂/p-Si heterostructures with SiGe nanoclusters was found to be caused by variations of the electrostatic potential in the near-suraface region of p-Si substrate and optically-induced spatial redistribution of trapped positive charges between SiO₂/Si interface levels and localized states of Ge nanoislads.

Adsorption complexes of germanium on the reconstructed Si(001)(4×2) surface have been simulated by the Si₉₆Ge₂Н₈₄ cluster. For Ge atoms located on the surface layer of the latter, DFT calculations (B3LYP, 6-31G**) of their 3d semicore-level energies have shown a clear-cut correlation between the chemical shifts and mutual arrangement of Ge atoms. Були досліджені фотогенерація і транспорт нерівноважних носіїв заряду і визначений механізмфотовідповіді в напівпровідникових SiGe/Si і SiGe/SiO2/Siр-гетероструктурах з наноострівцями. Зразки були вирощені методом молекулярно-променевої епітаксії. У роботі узагальнені результати досліджень морфологічних, структурних, оптичних та електричних властивостей гетероструктур з нанорозмірними об'єктами – квантовими точками і квантовими ямами. Показано, що фотопровідність наногетероструктури SiGe/Si в інфрачервоному діапазоні в залежності від компонентного складу, розмірів і величини механічних напружень в наноострівців Si1-xGex визначається міжзонними і внутрізонними переходами за участю локалізованих станів валентної зони Ge нанорозмірних об'єктів. Були встановлені ефекти фото- довгострокового розпаду і оптичного затухання провідності в SiGe/SiO₂/п-Si гетероструктур з SiGe нанокластерами, які викликані змінами електростатичного потенціалу в приповерхневій зоні р-Si підкладки і оптично-індукованого просторового перерозподілу захоплених позитивних зарядів між рівнями межі розділу SiO₂/Si і локалізованих станів Ge наноострівців.

Були вивчені адсорбційні комплекси германію на реконструйованій грані Si (001) (4×2) на прикладі кластера Si₉₆Ge₂Н₈₄. Для атомів Ge, локалізованих в приповерхневому шарі кластера, результати розрахунків методом ТФГ (B3LYP, 6-31G**) положення їх 3d-остовних рівнів свідчить про кореляцію між хімічним зсувом Ge (3d) і хімічним оточенням атомів германію. Были исследованы фотогенерация и транспорт неравновесных носителей заряда и определен механизм фотопроводимости в полупроводниковых SiGe/Si и SiGe/SiO₂/Siр-гетероструктурах с наноостровками. Структуры были выращены методом молекулярно-лучевой эпитаксии. В работе обобщены результаты исследований морфологических, структурных, оптических и электрических свойств гетероструктур с наноразмерными объектами – квантовыми точками и квантовыми ямами. Показано, что фотопроводимость наногетероструктуры SiGe/Si в инфракрасном диапазоне в зависимости от компонентного состава, размеров и величины механических напряжений в наноостровках Si1-xGex определяется межзонными и внутризонными переходами с участием локализованных состояний валентной зоны Ge наноразмерных объектов. Были установлены эффекты фото долгосрочного распада и оптического затухания проводимости в SiGe/SiO₂/п-Si гетероструктур с SiGe нанокластерами, которые вызваны изменениями электростатического потенциала в приповерхностной зоне р-Si подложки и оптически индуцированного пространственного перераспределения захваченных положительных зарядов между уровнями границы раздела SiO₂/Si и локализованных состояний Ge наноостровков.

Были изучены адсорбционные комплексы германия на реконструированной грани Si(001)(4×2) на примере кластера Si₉₆Ge₂Н₈₄. Для атомов Ge, локализованных в приповерхностном слое кластера, результаты расчетов методом ТФП (B3LYP, 6‑31G**) положения их 3d-остовных уровней свидетельствует о корреляции между химическим сдвигом Ge(3d) и химическим окружением атомов германия.